TRACTOVKAFILOSOFSKIKHPROBLEM TREATMENT OF PHILOSOPHICAL PROBLEMS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article deals with Stendhal's philosophy, aesthetics and psychology. However, Stendhal's main and most striking characteristic was a thirst for consistency, not a love of paradoxes and mental improvisation.